If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -28 + y = -3 Solving -28 + y = -3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + y = -3 + 28 Combine like terms: -28 + 28 = 0 0 + y = -3 + 28 y = -3 + 28 Combine like terms: -3 + 28 = 25 y = 25 Simplifying y = 25
| f(x)=x^2-64 | | 5X-(3X-2)=28 | | logx(2)=96 | | 4x^4-x^3-36x^2-111x+30=0 | | 3x+4=x+23 | | 100+9x=210+6x | | 3(y-2)=2(y+5) | | f(5)=3x^2-6x+4 | | 27x+13y+91z=667 | | 27x+6y=17 | | 135+23x=1+45x | | y-12=2 | | 4(-3v-1)-4=88 | | -6-5y=13 | | 35y+7=17 | | (2x+1)(x-5)=2x^2-1 | | xn=3n+11 | | 7(7b-3)=-413 | | (z-4)(z-10)=0 | | 7(x^2+1)=50x | | 36+4p=-4-3(p-4) | | n+4n=250 | | 4+b=2 | | 3x^2-x=-7x | | 9x+3=24 | | 3x(6+4)= | | k-10fork=25 | | x^5-3x^4-x^3+3x^2-6x+18=0 | | 1x=10-1y | | 12y+4=8(y-7) | | 116=x+(2x+1)+(4x+3)+(8x+5) | | 116=x+(2x+1) |